2008
DOI: 10.1097/wnr.0b013e328300edf3
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-based morphometry study on brain structure in children with high-functioning autism

Abstract: Earlier studies have suggested abnormal brain volumes in autism, but inconsistencies exist. Using voxel-based morphometry, we compared global and regional brain volumes in 17 high-functioning autistic children with 15 matched controls. We identified significant reduction in left white matter volume and white/gray matter ratio in autism. Regional brain volume reductions were detected for right anterior cingulate, left superior parietal lobule white matter volumes, and right parahippocampal gyrus gray matter vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 24 publications
7
51
2
Order By: Relevance
“…Higher than normal density, not observed by us, has been reported in inferior frontal cortex 10,13 and cerebellum. 3,8,14 Other investigations identified areas of higher or lower GM density that were unaffected in our patients, such as the amygdala, 8 cingulate gyrus, 8,11 fusiform gyrus, 10,14 and thalamus. 5,12,13 GM reduction in the basal forebrain, which is the most remarkable finding of our study, was not observed previously.…”
Section: Discussionmentioning
confidence: 95%
“…Higher than normal density, not observed by us, has been reported in inferior frontal cortex 10,13 and cerebellum. 3,8,14 Other investigations identified areas of higher or lower GM density that were unaffected in our patients, such as the amygdala, 8 cingulate gyrus, 8,11 fusiform gyrus, 10,14 and thalamus. 5,12,13 GM reduction in the basal forebrain, which is the most remarkable finding of our study, was not observed previously.…”
Section: Discussionmentioning
confidence: 95%
“…Altogether, we included 15 studies describing regional grey matter volume differences. 30,32,35,38,41,[59][60][61][62][63][64][65][66][67][68] Of these, 3 studies compared both people with Asperger syndrome and autism separately with J Psychiatry Neurosci 2011;36(6) controls. 30,32,41 The final autism group comprised 9 studies (Table 1) with 151 patients (mean age 18 yr) and 190 controls (mean age 17 yr).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, several studies have reported smaller local GM volumes in frontalstriatal and cerebellar regions (McAlonan et al, 2002) and the superior temporal sulcus (STS) (Boddaert et al, 2004). Both enlarged GM volumes in some areas and smaller volumes in other areas have also been reported (Rojas et al, 2006;Ke et al, 2008).…”
Section: Introductionmentioning
confidence: 91%